An evaluation methodology with applied life-cycle assessment of coal-biomass cofiring in Philippine context - Martinez, Dan William C. (Animo Repository, 2017)
The present study proposes an evaluation methodology assessing the environmental impact of coal-biomass cofiring with three major stages: resources and logistics mapping, environmental life-cycle assessment and results analysis and prediction. It presents novelty through the inclusion of the first stage which evaluates the actual biomass resource availability and logistics. It also reviews the technological capabilities and limitations for cofiring. It appends the third stage which predicts the optimal conditions for the local deployment of coal-biomass cofiring. Three types of locally available biomass were evaluated for theoretical and technical potential: primary and secondary agricultural residues, forest biomass and energy crop. Primary agricultural residue or rice straw is the most dependable biomass which can replace 7.53% of the total fuel energy input from coal. The study then sets three evaluation scenarios: the base case scenario of pure coal combustion and the two cofiring scenarios at 5% and 7.53% biomass share. Impact assessment reveals a GHG emission of 2.93 Mtons of CO2 eq. per year from pure coal combustion, 2.81 Mtons from cofiring at 5% biomass share and 2.74 Mtons from cofiring at 7.53% biomass share. GHG emission is lowest from cofiring at 7.53% biomass share which can potentially reduce the emission from pure coal combustion by 6.62%. Cofiring at 5% biomass share can potentially reduce the emission by 4.39%. In terms of nonrenewable energy consumption, coal combustion consumes 28.06 GJ of primary energy whereas cofiring at 5% biomass share consumes 26.69 GJ of primary energy and cofiring at 7.53% consumes 25.99 GJ of primary energy. Cofiring at 5% and 7.53% biomass share presents 4.90% and 7.38% reduction in nonrenewable energy consumption from the base case. Meanwhile, sensitivity analysis shows that biomass availability is the most significant factor that affects the reduction of GHG emission and nonrenewable energy consumption in cofiring. The share of biomass in total energy input is another significant factor that affects cofiring. Coal quality and rice straw quality in terms of heating value show slightly significant impact. The transportation distance and diesel consumption for biomass logistics have very minimal effect in the environmental impact of the whole cofiring system.